Diseño e implementación de un laboratorio de máquinas eléctricas en la Universidad Técnica de Cotopaxi sede La Maná, del cantón La Maná, provincia de Cotopaxi, año 2013 - Paredes Moran, Darwin Vinicio (2014)
This thesis has as aim the design and implementation of a laboratory for electric machines to practice with induction motors for the Engineering and Applied Sciences Career in Cotopaxi Technical University La Maná. Many factors were studied that allow realizing the investigation in order that students through these practices enrich adequately their theoretical- practical knowledge in the labs; developing skills and abilities which permits being updated with the different technological advances.